Two commercial music radio stations and their use of Twitter - Smurthwaite, Michael (My University, 2016)
This research report is an exploratory study into two regional commercial music stations (YFM and 947) and their use of Twitter as a tool to relate to, interact with and enable participation from their audiences. Of particular interest was why they are using it, what they are doing with it and how this affects the on-air content pre, during and post broadcast, if at all it does. [Abbreviated Abstract. Open document to view full version]
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Arts (Journalism and Media Studies), 2016
Keywords: Twitter; Radio broadcasting--Social aspects; Popular music radio stations--South Africa; Social media--South Africa; Internet--Social aspects; Online social networks